PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK KETELADANAN KH. A. WAHAB HASBULLAH UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK BAHASA ARAB SISWA KELAS X DI MAN 10 JOMBANG - Dian Rahmawati , Rina; Ainur Rokma Wati, Lalei (CV. Lafadz Jaya, 2024)
This study aims to develop a learning media in the form of a comic featuring the exemplary figure KH. A. Wahab Hasbullah to improve the Arabic listening skills of tenth-grade students at MAN 10 Jombang. Comic-based learning media is expected to engage students' interest and provide a deeper understanding of the Arabic language material. This research adopts the research and development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of tenth-grade students from class X-C at MAN 10 Jombang, and data were collected through pre-tests and post-tests to measure the improvement in students' listening skills. The results showed that the average pre-test score was 65.37, while the post-test score significantly increased to 89.08. The N-Gain Score test indicated an effective improvement with a score of 69.76%, which falls into the moderately effective category. Validation from media experts and subject matter experts resulted in validity scores of 95% and 93.3%, respectively, demonstrating that the media is highly suitable for use. Additionally, students' responses to the learning media were overwhelmingly positive, with 94.06% agreeing that the comic media helped them understand Arabic listening materials. Therefore, this learning media effectively enhances students' listening skills and is suitable for use in the learning process.